The Effect of Breathing Exercise and Progressive Muscle Relaxation on Improving Sleep Quality in Postmenopausal Women - Cahyaningrum, Hapsari; Sari, Apriliyan Yunita; Umatin, Khoiru (Poltekkes Kemenkes Jakarta III, 2025)
Sleep disturbances are common among menopausal women and negatively affect quality of life, cognitive function, and emotional well-being. The decline in estrogen and progesterone during menopause often leads to insomnia, hot flashes, and anxiety. Non-pharmacological approaches such as Progressive Muscle Relaxation (PMR) and Breathing Exercise (BE) are considered effective, yet studies combining both methods remain limited, particularly in community-based settings. This study aimed to evaluate the effect of combined PMR and BE on sleep quality in menopausal women within an Integrated Health Post for the Elderly (Posyandu Lansia) community. A preexperimental one-group pretest–posttest design was used. Twenty-six menopausal women, members of the Posyandu Lansia Dahlia II in Surakarta, Indonesia, were recruited through total sampling. The intervention consisted of PMR and BE, conducted five times per week for eight weeks. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) before and after the intervention. Data were analyzed using the Wilcoxon Signed-Rank Test with a significance threshold of p < 0.05. Before the intervention, all participants reported poor sleep quality with an average PSQI score of 7.54. After eight weeks, 53.8% of participants showed good sleep quality, with the average PSQI score decreasing to 6.12. Statistical analysis revealed a significant difference between pre- and post-intervention scores (p = 0.0001). In conclusion, the combination of PMR and BE significantly improved sleep quality in menopausal women and may serve as an effective, low-cost, community-based health promotion strategy.